Asymmetries in nucleon transfer reactions induced by polarized protons - Nelson, J (1968)
Nucleon transfer reactions play an important part in studies of nuclear spectroscopy, and it is necessary that the basic reaction theory should be thoroughly examined. In the case of two nucleon transfer reactions, this examination has been confined to the differential cross section since a proper study of polarization phenomena in these reactions has not been made. In this thesis, the results of a number of asymmetry measurements in double pick-up reactions will be reported. These measurements, based on (p,t) and (p,3He) experiments, were performed at the Rutherford High Energy Laboratory using the 50 MeV polarised proton beam from the linear accelerator. During the course of this report, the techniques of experimentation with such a beam will be described. The differential cross sections of the reactions were measured with the more intense unpolarised beam, and these results will also be presented. An analysis of the data in terms of the distorted wave Born Approximation theory will be given in Chapter 5. The theory, in its two most frequently used forms, is outlined in Chapter 1. Special attention is paid to the consequences of neglecting spin-orbit coupling in the description of the optical model potentials. A summary is given in Chapter 2 of a general, spin-dependent distorted wave computer programme which was written as part of this research so that the DWBA analysis could be made. The programme is based on a code initially written specifically for deuteron stripping. In the analysis, it will be shown that the usual zero-range spin-independent form of the nucleon transfer process is unable to account for the experimental observations. The two forms of double pick-up theory will be compared, and the possibility of avoiding the zero-range approximation will be investigated. In fact, it will be seen that finite-range corrections are essential to a proper analysis of the data. The importance of interference effects and spin-orbit coupling in two nucleon transfer reactions will b« evaluated. The results of two optical model analyses of published cross section data are included in a discussion of the triton and 3He optical potentials. Finally, a possible new method of examining the relative phases of nuclear wave function components will be described.